Green synthesis and characterization of ZnO nanoparticles for photocatalytic degradation of anthracene. (13th November 2015) - Hassan, Saad S M; El Azab, Waleed I M; Ali, Hager R; Mansour, Mona S M
Abstract: Zinc oxide nanoparticles were prepared using corriandrum sativum leaf extract and zinc acetate dihydrate. It was utilized as a photocatalyst for the degradation of anthracene. The catalyst was characterized by x-ray diffraction, high-resolution transmission electron microscopy, scanning electron microscopy, dynamic scattering light, Raman spectrometry and UV–vis spectrophotometry. The catalyst was used in a bench-scale design for degradation of anthracene. The factors affecting the photocatalytic degradation efficiency, including irradiation time, loading catalyst doses, and initial concentration of anthracene were investigated. The results obtained showed that the photocatalytic degradation efficiency was increased with both the decrease of the initial anthracene concentration and the increase of the photocatalyst doses. The optimum photocatalytic degradation was obtained at pH 7, irradiation time of 240 min and loading catalyst dose of 1000 μ g L −1 . Under these conditions, the photocatalytic degradation percentage of anthracene was 96%. The byproduct was the much less toxic (9, 10-anthraquinone) and a small amount of phthalic acid as confirmed by gas mass spectrometry and high-pressure liquid chromatography. The kinetic studies revealed that the photocatalytic degradation process obeyed the Langmuir–Hinshelwood model and followed a pseudo-first-order rate expression.